Canaanite Genocide and Palestinian Nakba in Conversation: A Postcolonial Exercise in Bi-directional Hermeneutics - Fisk, Bruce N. (Journal of Holy Land and Palestine Studies, 2019)
David Ben-Gurion's attempt to forge a collective Israeli identity rooted in the biblical conquest myth adopted a bi-directional hermeneutic: biblical text and modern reality were mutually illuminat...